1990
DOI: 10.1002/hep.1840110523
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and CCI4-induced liver injury, but not acidosis, impair metabolism of cysteinyl leukotrienes in perfused rat liver

Abstract: Uptake, metabolism and biliary elimination of infused cysteinyl leukotrienes were investigated in single-pass perfused rat liver. Hypoxia did not impair uptake of infused [3H]leukotriene C4, but inhibited biliary excretion of radioactivity by about 50% compared with normoxic control experiments. In addition, the leukotriene metabolite pattern in bile was profoundly altered and was characterized in hypoxia by a 75% to 80% decrease of both leukotriene C4 and polar metabolites, representing omega-oxidation produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Using a different HPLC system, the polar fraction separated into different metabolites co-eluting with standards of w-oxidation products of N-acetyl-LTE4 [22]. Less than 3% of the radioactivity taken up was excreted into bile as N-acetyl-LTE,, whereas LTE4 was not detectable in bile.…”
Section: Sulfobromophthalein and Taurocholate Change The Pattern Of Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a different HPLC system, the polar fraction separated into different metabolites co-eluting with standards of w-oxidation products of N-acetyl-LTE4 [22]. Less than 3% of the radioactivity taken up was excreted into bile as N-acetyl-LTE,, whereas LTE4 was not detectable in bile.…”
Section: Sulfobromophthalein and Taurocholate Change The Pattern Of Bmentioning
confidence: 99%
“…In a mutant rat strain with a hereditary defect in biliary excretion of conjugated bilirubin and dibromosulfophthalein, elimination of cysteinyl leukotrienes was also impaired, whereas taurocholate excretion was normal [15-171. Understanding of hepatic leukotriene processing is of importance in view of the previous observations that impairment of hepatic leukotriene elimination may be a major pathophysiological mechanism in diseases like endotoxin shock [18,191, the hepatorenal syndrome [20] and ethanolinduced hepatitis [21]. Hepatic leukotriene processing is also impaired under conditions leading to liver hypoxia and liver cell necrosis [22]. In addition, inhibition of sinusoidal uptake or biliary excretion of cysteinyl leukotrienes may be responsible for side-effects of drugs like cyclosporin [23].…”
mentioning
confidence: 99%
“…Experimental hepatic injury (EHI) induced by a single administration of carbon tetrachloride (CCl 4 ) has been widely used as a pathological model for liver diseases, since it is known that CCl 4 produces acute hepatocellular injury with centrilobular necrosis and steatosis (Recknagel, 1967). The effects of CCl 4 -EHI on biochemical characteristics such as increased lipid peroxidation (Recknagel, 1967) and the activities (Mourelle et al, 1987;Romero et al, 1994) of glutamic oxaloacetic transaminase (GOT) and glutamic pyruvic transaminase (GPT) and hepatobiliary excretion of xenobiotics (for example, sulfobromophthalein and leukotriene; Iga et al, 1977;Wettstern et al, 1990) have been widely studied. Our earlier study revealed that transport systems for some organic cations on the sinusoidal membrane are prone to damage as the result of CCl 4 -EHI, as demonstrated by a decrease in the in vitro maximal rates of hepatic uptake and efflux without any influence on in vivo canalicular excretion clearance (Hong et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…No evident increase or decrease in the level of ALP was observed. Absence of any concomitant increase of decrease on the ALP levels, under experimental conditions, was attributed to the fact that the single dose, intraperitioneal injection of the carbon tetrachloride at the pre-stated concentration/dosage, may not have caused any significant (P<0.05) billiary tract obstruction or disease [158] while causing acute hepatocellular injury [159]. Also the protective role of Gongronema latifolium in acetaminophen induced hepatic toxicity in Wistar rats was elucidated by [160].…”
Section: Gongronema Latifoliummentioning
confidence: 99%